1999
DOI: 10.1152/jappl.1999.87.3.977
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine as selective β1-adrenoceptor agonist in in vivo studies on human thermogenesis and lipid utilization

Abstract: The use of dobutamine as selective beta(1)-adrenoceptor agonist in in vivo studies on human thermogenesis and lipid utilization was investigated in 20 men. At 2.5, 5, and 10 microg x kg(-1) x min(-1), dobutamine induced significant increases in energy expenditure, lipid oxidation, and lipolysis. The beta(1)-adrenoceptor antagonist atenolol (bolus: 42.5 microg/kg, infusion: 1.02 microg x kg(-1) x min(-1)) blocked all dobutamine-induced effects on thermogenesis and lipid utilization. All parameters remained at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…The maximum dose we used was 9 g/kg FFM⅐min, which is comparable with 7.5 g/kg BW⅐min and thus lies within the range of ␤ 1 -adrenoceptor specificity. Our earlier study (9) also showed that the ␤ 2 -adrenoceptor agonist salbutamol in a concentration of 85 ng/kg BW⅐min (or 100 ng/kg FFM⅐min) also induced ␤ 1 -adrenoceptor-specific changes in lipid utilization. Addition of the ␤ 1 -adrenoceptor antagonist atenolol prevented simultaneous ␤ 1 -adrenergic stimulation, but did not affect ␤ 2 -adrenoceptor-specific changes.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The maximum dose we used was 9 g/kg FFM⅐min, which is comparable with 7.5 g/kg BW⅐min and thus lies within the range of ␤ 1 -adrenoceptor specificity. Our earlier study (9) also showed that the ␤ 2 -adrenoceptor agonist salbutamol in a concentration of 85 ng/kg BW⅐min (or 100 ng/kg FFM⅐min) also induced ␤ 1 -adrenoceptor-specific changes in lipid utilization. Addition of the ␤ 1 -adrenoceptor antagonist atenolol prevented simultaneous ␤ 1 -adrenergic stimulation, but did not affect ␤ 2 -adrenoceptor-specific changes.…”
Section: Discussionmentioning
confidence: 69%
“…The interpretation of the data from our study highly depends on the selectivity of the ␤-adrenoceptor agonists used. An earlier study from our group (9) showed that dobutamine induced ␤ 1 -adrenoceptor-specific changes in thermogenesis and lipid utilization in dosages of 10 g/kg BW⅐min or less. The maximum dose we used was 9 g/kg FFM⅐min, which is comparable with 7.5 g/kg BW⅐min and thus lies within the range of ␤ 1 -adrenoceptor specificity.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…5,6 During selective b 1 -adrenergic stimulation, lipolysis, lipid oxidation and energy expenditure increase. 7,8 Free fatty acids (FFA), needed for lipid oxidation, are released from the adipose tissue by stimulating its b 1 -adrenoceptors. The increase in lipid oxidation and thermogenesis is assumed to be localized predominantly in skeletal muscle, 9,10 but this tissue contains mainly b 2 -adrenoceptors and presumably no b 1 -adrenoceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy young men treated with a synthetic beta-3 agonist had a reduction in 24-h RQ, 90 indicating an increase in fat oxidation. In addition, infusions of betaadrenergic agonists not only increase energy expenditure but also increase fat oxidation 91,92 and improve insulin sensitivity. As such, it is possible that the sympathetic nervous system (SNS), acting through the beta-3 adrenoreceptor or other adrenoreceptors, regulates fat oxidation.…”
mentioning
confidence: 99%